Effects of zotepine on extracellular levels of monoamine, GABA and glutamate in rat prefrontal cortex - Yamamura, S (Blackwell Publishing Ltd, 2009)
BACKGROUND AND PURPOSE: The atypical antipsychotic drug, zotepine, is effective in treatment of schizophrenia and acute mania, but the incidence of seizures during treatment is higher than with other antipsychotics. In addition, the mechanisms underlying the clinical actions of zotepine remain uncharacterized. EXPERIMENTAL APPROACH: The effects of intraperitoneal administration of zotepine and haloperidol on the extracellular levels of noradrenaline, dopamine, 5-HT, GABA, and glutamate in the medial prefrontal cortex (mPFC) were compared. Neuronal activities induced by each drug in the ventral tegmental area (VTA), locus coeruleus (LC), dorsal raphe nucleus (DRN) and mediodorsal thalamic nucleus (MTN) were also analysed. KEY RESULTS: Haloperidol did not affect extracellular neurotransmitter levels in the mPFC. In contrast, zotepine activated neuronal activities in all nuclei and increased the extracellular levels of noradrenaline, dopamine, GABA, and glutamate in the mPFC, but not 5-HT levels. The zotepine-stimulated neuronal activity in the VTA, LC, DRN and MTN enhanced the release of dopamine, noradrenaline, 5-HT, glutamate and GABA in the mPFC, although the enhanced GABAergic transmission possibly inhibited noradrenaline, dopamine and 5-HT release. The other afferent to mPFC, which releases dopamine and noradrenaline, was partially insensitive to GABAergic inhibition, but possibly received stimulatory AMPA/glutamatergic regulation from the MTN. CONCLUSIONS AND IMPLICATIONS: Our results indicated that the positive interaction between prefrontal catecholaminergic transmission and AMPA/glutamatergic transmission from MTN might explain the regulatory effects of zotepine on neurotransmitter release. A mechanism is suggested to account for the pharmacological profile of this atypical antipsychotic and for its pro-convulsive action. British Journal of Pharmacology (2009) 157, 656–665; doi:10.1111/j.1476-5381.2009.00175.x; published online 9 April 2009